2006
DOI: 10.1016/j.intimp.2005.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A new chapter opens in anti-inflammatory treatments:The antidepressant bupropion lowers production of tumor necrosis factor-alpha and interferon-gamma in mice

Abstract: In a wide range of human diseases of inflammatory nature like Crohn's disease, pathology is mediated in part by pro-inflammatory cytokines like tumor necrosis factor-alpha (TNF) or interferon-gamma. We show here that a commonly used generic antidepressant bupropion, in wide use worldwide to treat depression in humans for a decade now, profoundly lowers levels of TNF, interferon-gamma, and interleukin-1 beta in vivo, in a mouse lipopolysaccharide (LPS) induced inflammation model. Mice challenged with an otherwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(117 citation statements)
references
References 20 publications
5
103
0
6
Order By: Relevance
“…In particular, treatments directed at the targets identified here have the potential not only to treat depression but also to treat certain medical comorbidities that occur alongside depression. [47,49,170] Interestingly, even traditional antidepressant medications, which putatively work via monoaminergic actions, affect many of the novel targets described here [95,109,128,[171][172][173][174][175][176][177] (see Fig. 1), even though they were not developed with those purposes in mind.…”
Section: Do Stress and Depression Accelerate Cell Aging?mentioning
confidence: 99%
“…In particular, treatments directed at the targets identified here have the potential not only to treat depression but also to treat certain medical comorbidities that occur alongside depression. [47,49,170] Interestingly, even traditional antidepressant medications, which putatively work via monoaminergic actions, affect many of the novel targets described here [95,109,128,[171][172][173][174][175][176][177] (see Fig. 1), even though they were not developed with those purposes in mind.…”
Section: Do Stress and Depression Accelerate Cell Aging?mentioning
confidence: 99%
“…While we attempted to overcome this limitation by evaluating the effects of the common antidepressant fluox etine on KP metabolites in rats, different classes of antidepres sant medications may have affected the present results. [59][60][61] Other variables known to affect inflammatory markers, such as body mass index, were not available for statistical corrections. While our histopathological analysis revealed no major signs of activated M1 amoeboid microglia, other microglial abnormal ities, particularly at the neurovascular interface, could not be adequately quantified in the present study.…”
Section: Limitationsmentioning
confidence: 99%
“…Therefore, the synergistic effects of Suc and Cp may not only affect adipose tissue but also peripheral macrophages. Furthermore, Brustolim et al (50) reported that the antidepressant bupropion, which is a norepinephrine and dopamine weak reuptake inhibitor, may suppress TNF-α synthesis by mediating increased signaling β-adrenoreceptors and dopamine type 1 receptors, resulting in increased cAMP that inhibits TNF-α synthesis. In addition, Cloëz-Tayarani et al (51) reported that serotonin inhibited TNF-α production human peripheral blood mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%